Representative Fiction in Muslim Literature in South Africa - Paruk, Fathima (University of the Witwatersrand, Johannesburg, 2024)
This research explores Muslim representative fiction in South Africa, addressing the challenges of limited local readership and reliance on imported content in the South African Muslim publishing sector. It emphasises the need for more representative adult fiction and investigates how independent and hybrid models can amplify diverse Muslim voices. The study employs semi-structured interviews, analyses books by self-identifying Muslim authors, and uses Nielsen Book Data and the Muslim Book Reviewers (MBR) scale to examine epitextual and paratextual elements. Key findings indicate that local Muslim publishers face challenges such as small market size, limited readership, competition with international publishers, and distribution and marketing issues. To address these challenges, it is recommended to conduct regular surveys and focus groups to understand evolving preferences, strengthen networks with local retailers, expand online presence and social media marketing, improve publication quality to meet international standards and ensure culturally relevant and diverse content. Promoting local authors, investing in underrepresented genres, and fostering collaborations with community members and educational institutions are also essential for enhancing the quality, impact, and market reach of Muslim fiction
A research report Submitted n fulfillment of the requirements for the degree of Masters in Publishing, In the Faculty of Humanities , School of Language, Literature and Media, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Muslim fiction; representative fiction; publishing; SDG-4: Quality education